Synthesis of 1-[3-(Cyclopentyloxy)-4-methoxyphenyl]cyclopentanol as Potential Phosphodiesterase-4 Inhibitor - Yahya-Meymandi, A.; Mohammadi Ziarani, G.; Shafiee, A.; Foroumadi, A. (Asian Journal of Chemistry, 2011)
The enzyme phosphodiesterase-4 (PDE4) plays a key role in many physiological or pathological processes in mammalian organs, where its inhibition increases cyclic adenosine monophosphate (cAMP) causing benefits in many diseases or conditions. The aim of this study is to synthesize 1-(3-(cyclopentyloxy)-4-methoxyphenyl)cyclopentanol (6) as potential phosphodiesterase-4 inhibitor. Starting from 2-methoxy phenol (1), 4-bromo-2-(cyclopentyloxy)-1-methoxybenzene (5) was synthesized in good yields. 1-[3-(Cyclopentyloxy)-4-methoxyphenyl]cyclopentanol (6) was prepared from 5 using two different methods.